If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 61 + x = 7 Solving 61 + x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-61' to each side of the equation. 61 + -61 + x = 7 + -61 Combine like terms: 61 + -61 = 0 0 + x = 7 + -61 x = 7 + -61 Combine like terms: 7 + -61 = -54 x = -54 Simplifying x = -54
| 8+2(z-4)=-7z+7 | | cos^2x-5cosx-4=0 | | cosx^2-5cosx-4=0 | | 3y+4z=130 | | -3(-7x-6)+11x=14-(10x-19) | | -0.7=-0.7+0.6u | | 10-3(2r-1)=1 | | 5/2×2-7 | | 1/2(-10r) | | x=(x*4)-875 | | X/6=0.5 | | 15+(-18)=7x-3-6x | | ln(1/72)=y | | xsquare=40 | | 4x=1/10 | | 24s=528 | | 16n=192 | | 3s^2+8s+3=0 | | 8y-3=(2y+1) | | C-7=14 | | 0.07+4x=2 | | 3x-8=4x+(-4) | | 19(sin(x))+9=sin(x) | | 7x/5x^2 | | x^((1)/(3))-x^((1)/(6))=0 | | (200x-3000)/200x=.30 | | (D^4+1)y=0 | | 8(3a-9)-4(2a+3)=12 | | x/2-1/44-44 | | 10ln(4)+ln(X)=16 | | 7x=-16-9 | | 15s+8.4-2s=8.4-s |